Infectious Process and Sepsis - Neri, Vincenzo (IntechOpen, 2020)
Sepsis is a very complex clinical condition that can be considered the central point of the infectious process: the arrival point in the evolution of a localized septic outbreak that has caused a systemic inflammatory reaction. In the clinical setting two important questions regarding the transition from local inflammation, with beneficial effect, to systemic inflammatory disease, with deleterious results, remain unanswered. First, why does the transition from local to systemic disease only occur in some subjects? Second, how long does this transition take? This book attempts to answer these questions. Chapters cover such topics as surgical infections, microbiota therapy in sepsis, cytokines for host immune response, and the role of serum amyloid A in the acute phase of sepsis.